INVESTIGATING THE POTENTIAL INFLUENCE OF C IN MAKING YOUNG PEOPLE'SCHOICESIN THE CONTEXT OF BRAND SENSITIVITY - Amin, Sara; Liaquat, Malka; Malik, Samra (The journal of contemporary issues in business and government, 2022)
According to the research, clothing with well-known brand names appears to be crucial for young buyers. Regarding Pakistani young people's brand sensitivity, this study investigated how two socialization agents influenced the development of Pakistani young people's comparative importance and sensitivity to brand messages. T-tests and regression analyses were carried out on participants between the ages of 18 and 24. According to the findings, social media and peer influence are significant indicators of young people's brand sensitivity, particularly among boys. According to the study's conclusions, social media is a more socializing solid agent in today's modern period than in previous periods. According to these data, young ladies appear to be more brand-conscious than young males in clothing. The data has been analyzed to emphasize peer pressure and social media advertising to attract a more youthful demographic.